Sodium butyrate inhibits osteogenesis in human periodontal ligament stem cells by suppressing smad1 expression - Jingyi Hou; Junji Xu; Yi Liu; Haiping Zhang; Sihan Wang; Yao Jiao; Lijia Guo; Song Li (BMC, 2022)
Abstract Background Butyrate is a major subgingival microbial metabolite that is closely related to periodontal disease. It affects the proliferation and differentiation of mesenchymal stem cells. However, the mechanisms by which butyrate affects the osteogenic differentiation of periodontal ligament stem cells (PDLSCs) remain unclear. Here, we investigated the effect of sodium butyrate (NaB) on the osteogenic differentiation of human PDLSCs. Methods PDLSCs were isolated from human periodontal ligaments and treated with various concentrations of NaB in vitro. The cell counting kit-8 assay and flow cytometric analysis were used to assess cell viability. The osteogenic differentiation capabilities of PDLSCs were evaluated using the alkaline phosphatase activity assay, alizarin red staining, RT-PCR, western blotting and in vivo transplantation. Results NaB decreased PDLSC proliferation and induced apoptosis in a dose- and time-depend manner. Additionally, 1 mM NaB reduced alkaline phosphatase activity, mineralization ability, and the expression of osteogenic differentiation-related genes and proteins. Treatment with a free fatty acids receptor 2 (FFAR2) antagonist and agonist indicated that NaB inhibited the osteogenic differentiation capacity of PDLSCs by affecting the expression of Smad1. Conclusion Our findings suggest that NaB inhibits the osteogenic differentiation of PDLSCs by activating FFAR2 and decreasing the expression of Smad1.